(untitled) (MAUSAM, 1998)
The effective outgoing terrestrial radiant energy controls the variations in other meteorological parameters near the ground surface. In the absence of direct measurements of this energy, the values are derived from other radiation parameters that are being measured at Pune. On an average day the loss of this terrestrial energy is of the order of 8.5 MJm-2. The maximum of 12.53 MJm-2 is reached in April and the minimum of 3.87 MJm-2 during August. The daily maximum occurs at noon or just after that. Year-to-year variations however depend on the rainfall distribution and the moisture in the air.